Mediated immediacy : published diaries of World War II as media of war memory in East and West Germany 1945-1990 - Boden, Anne (Trinity College (Dublin, Ireland). Department of Germanic Studies, 2009)
This study explores the specific role played by published diaries in the negotiation and renegotiation of public war memories in East and West Germany from 1945 to re-unification. It does so by asking which war diaries were published in the GDR and the Federal Republic, which public narratives of specific war events they collaborated or contested, and what public response they elicited at different times, and in different contexts. Following a more general survey of these questions in my introduction, I focus on three case studies to illustrate how war diaries were shaped by and in turn also shaped memory discourses current at the time of their publication in East and West Germany.
Keywords: Germanic Studies, Ph.D.; Ph.D. Trinity College Dublin.